Methods of investigation of crime: current state, problems of construction and direction of improvement - Khlus, A.M. (Bulletin of the Karaganda University “Law Series”, 2024)
The article considers the problem of methodological support for the preliminary investigation stage of crimes. Attention is focused on individual problematic aspects of the forensic characteristics of crimes, the further development of which does not contribute to self-improvement. Modern investigation methods based on the forensic characteristics of crimes do not meet the needs of the time due to the imperfection of this scientific category. According to the author, the formation of private methods of investigating crimes should be preceded by the initial identification and then characterization (description) of the material elements that make up the structure of any criminal act. Such an approach contributes to the objective construction of an information-theoretical model of a crime used for the purposes of developing a private investigation methodology. The general elements of the material structure of crimes are named and briefly presented, a certain combination of which makes up the structure of the act under investigation. Information about them can serve as a basis for improving the methodological support for investigating crimes, as well as optimizing the activities of investigating criminal cases. The author is of the opinion that it is inappropriate to abandon the forensic characteristics of crimes, but considers it necessary to transform it on the basis of the formed doctrine of the material structure of a crime. A proposal has been made to consider the elements of the material structure of crimes in an inseparable unity with their forensic characteristics. This approach allows us to speak of a qualitatively new concept: the forensic characteristics of the material structure of a crime. As an informationtheoretical model of a crime, the forensic characteristics of its material structure on an objective basis will contribute to the development of new and improvement of existing methods of investigating criminal acts.